Answer:
--6+36m
Step-by-step explanation:
Well, you can cancel out the b and e, so a/c = f/d.
Then you cancel out a on the left side of the equation by multiplying both sides by 1/a which then gives you c = f/ad.
Hope this helps!
Answer with Step-by-step explanation:
Since we have given that
a + b = c
and a|c
i.e. a divides c.
We need to prove that a|b.
⇒ a = mb for some integer m
Since a|c,
So, mathematically, it is expressed as
c= ka
Now, we put the above value in a + b = c.
So, it becomes,
![a+b=c\\\\a+b=ka\\\\b=ka-a\\\\b=a(k-1)\\\\\implies a|b](https://tex.z-dn.net/?f=a%2Bb%3Dc%5C%5C%5C%5Ca%2Bb%3Dka%5C%5C%5C%5Cb%3Dka-a%5C%5C%5C%5Cb%3Da%28k-1%29%5C%5C%5C%5C%5Cimplies%20a%7Cb)
a=mb, here, m = k-1
Hence, proved.
12x=x^2-64
you have to do quadratic formula